The managerial duties of the nurse in charge of a unit in combating the spreading of HIV/AIDS - D. Isaacs; K. Jooste (AOSIS, 2004)
The charge sister has an essential role to play in combating the spreading of the HIV in the environment of the nursing unit. The HIV/AIDS dilemma is a reality in the health care environment. On a daily basis nurses is treating patients with the HIV. Through the basic conceptual framework of the management process, the charge sister can play her part and contribute in keeping the disease under control in her work environment. An explorative, descriptive study was done through a structured questionnaire with four open questions. This study was aimed at developing and formulating guidelines to be included in a policy to be used in the combating of spreading of HIV in the health care unit by the charge sister and her staff. The results indicate the absence of policy regarding the prevention of the spreading of the HIV, necessary for orientation and in service training of staff.